Clarification needed from Patterson Pumps (the manufacturer) regarding a major difference between the pumps ordered by BRAC University and pumps delivered by the contractor at project site - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the clarification needed from Patterson Pumps (the manufacturer) regarding a major difference between the pumps ordered by university authority and pumps delivered by the contractor at BRACU new campus project site.